EDUKASI BENTANG LAHAN BUKIT KEHI DAN KERTAGENA DAYA, KABUPATEN PAMEKASAN - Wagistina, Satti; Suharto, Yusuf; Hartono, Rudi; Syafitri, Dyah Rina; Kamal, Muhammad Mustafa Faiz; Joyti, Joyti; Putra, Bramantiyo K Dwi (Universitas Padjadjaran, 2025)
The first objective of the Community Service (PkM) activity is to educate the managers of the Bukit Kehi Tourism Awareness Group (Pokdarwis) about the geological and geomorphological features (landscape). The second objective is to assist Pokdarwis managers in planning the development of tourist attractions. The method used is training with an andragogical approach. The learning medium used is a 25-page landscape flipbook. The activity stages include planning, preparation, implementation, and evaluation. As a result, Pokdarwis has increased its knowledge of the landscape of Kertagena Daya and Bukit Kehi. This knowledge is very important for Pokdarwis in the context of developing tourist attractions. However, to provide landscape education services to visitors, Pokdarwis requires a learning process to effectively introduce geological and geomorphological features. The development of Bukit Kehi tourism is planned to become geotourism, so in the future, assistance from the PkM team will be needed for Pokdarwis. Tujuan pertama kegiatan Pengabdian kepada Masyarakat (PkM) ini adalah memberikan pengetahuan dan melatih pengelola Kelompok Sadar Wisata (Pokdarwis) Bukit Kehi tentang fitur geologi dan geomorfologi (bentang lahan). Tujuan kedua adalah mendampingi pengelola Pokdarwis merencanakan pengembangan obyek wisata. Metode yang digunakan adalah pelatihan dengan pendekatan andragogi. Media belajar yang digunakan adalah flipbook bentang lahan dengan jumlah 25 halaman. Tahapan kegiatan meliputi perencanaan, persiapan, pelaksanaan, dan evaluasi. Hasil kegiatan PkM adalah terjadi peningkatan pengetahuan bentang lahan Desa Kertagena Daya dan Bukit Kehi. Pengetahuan ini sangat penting dimiliki oleh Pokdarwis dalam rangka pengembangan atraksi wisata. Namun, untuk memberikan layanan edukasi bentang lahan kepada para pengunjung, dibutuhkan proses belajar pengenalan fitur geologi dan geomorfologi. Pengembangan wisata Bukit Kehi direncanakan menjadi geowisata sehingga ke depan dibutuhkan pendampingan kepada Pokdarwis oleh tim PkM.